Computational modeling of atmospheric dispersion applied to a small modular reactor - Curzio, Rodrigo Carneiro; Moura, Bruno da Silva; Saldanha, Pedro Luiz da Cruz; Gavazza, Sergio (International Journal of Advanced Engineering Research and Science, 2020)
This study describes the computational modeling of the atmospheric dispersion resulting from a postulated radiological accident in a small modular reactor (SMR), with a power of 16 MWe (50 MWt), and containing three fuel enrichment regions, at 4%, 5 % and 20%. Among the hypothetical inventory radionuclides, derived from nuclear reactions during fuel burnup after 2 years of operation, the contribution of Cs-137 was considered for simulation, using the HotSpot code, of the concentration and total effective doses (TEDE) received, both depending on the distance from the event. A locality in the interior of Brazil was chosen to install the SMR, where information on meteorological conditions was collected to identify the predominant atmospheric stability class. The results suggest that the maximum calculated TEDE was 3.6 Sv, 34 m from the reactor, decreasing with time and distance, and following the Gaussian dispersion model, and that the contamination plume is dependent on the Pasquill-Gifford criteria and Cs-137 activity. For doses between 1 mSv and 10 mSv and between 10 mSv and 50 mSv, it is suggested that the population be housed in existing buildings in the locality, and for values above 50 mSv, shelter in these conditions or the evacuation of people close to the reactor in movement contrary to the spread of the plume. The relevance of this investigation shows the importance of emergency response planning and the influence of meteorological conditions, considering the data assumed in the simulation.